GE_GERICHTE P/6439/2021 vom 20. April 2023 - GE Cour de justice (2023)
DIFFAMATION;CALOMNIE;PRINCIPE DE LA BONNE FOI;PREUVE LIBÉRATOIRE;VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) | CPP.310; CP.173; CP.174; CP.139; CP.144